2018
DOI: 10.24193/subbchem.2018.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Heavy Metals in Plantago Major Grown in Urban and Post-Industrial Areas

Abstract: The enrichment and accumulation of heavy metals (Cu, Pb, Zn, Cd, Cr, Ni) in Plantago major leafs was comparatively studied in an urban (Cluj-Napoca) and a post-industrial area (Baia-Mare) from Romania. These two sites were selected for study as in Cluj-Napoca the dominant metal pollution sources are related to traffic, urban runoff, residential heating and municipal landfill, while in Baia-Mare the main pollution sources are the former ore processing activities and the remaining metal rich mining wastes. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…A previous study showed that soil samples in an urban area of Cluj-Napoca had on average Cu 41 mg/kg, Pb 53 mg/kg, Zn 125 mg/kg, Cr 46 mg/kg, and Ni 47.5 mg/kg [19], compared to these, the values in this study were lower. A study conducted in the country's capital (Bucharest) showed that three major urban parks had elevated Zn, Pb, and Cu levels, and although heavy metal concentration was heterogenous, the overall proximity to intense trafficways was proposed as a source of pollution [74].…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…A previous study showed that soil samples in an urban area of Cluj-Napoca had on average Cu 41 mg/kg, Pb 53 mg/kg, Zn 125 mg/kg, Cr 46 mg/kg, and Ni 47.5 mg/kg [19], compared to these, the values in this study were lower. A study conducted in the country's capital (Bucharest) showed that three major urban parks had elevated Zn, Pb, and Cu levels, and although heavy metal concentration was heterogenous, the overall proximity to intense trafficways was proposed as a source of pollution [74].…”
Section: Discussioncontrasting
confidence: 77%
“…HM pollution of urban soil in Europe showed that elevated levels of the most common five heavy metals were 22% of anthropogenic enrichment (such as traffic and industry) while 44% were of geogenic enrichment [ 10 ]. In Cluj-Napoca, the main source of metal pollution is related to traffic, urban run-off, residential heating, and municipal landfill [ 19 ]. The proximity to pollution sources can be a cause of increased soil pollution in the urban environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the study conducted by Kurteva (2009) recorded a higher Zn accumulation in the leaves of Plantago lanceolata. Our investigation of the accumulation of potentially toxic metals found much higher metal concentrations in the soil and leaves of Plantago major compared with the study in Cluj-Napoca, Romania, of Levei et al (2018).…”
Section: Resultssupporting
confidence: 44%
“…As for P. weldenii, there is rather limited evidence available for its tolerance towards PTEs. However, in different species within the family Plantaginaceae, there are related studies showing their resistance to contaminants [59,60]. It is noteworthy that Cd concentrations per fresh weight in S. oleraceus well exceeded the regulation limit of 0.2 mg kg −1 of category 3.2.15 ("leaf vegetables") of the Directive 86/278/EC, while those in P. weldenii did not, even when grown in such soil spiked with Cd at 45 mg kg −1 .…”
Section: Discussionmentioning
confidence: 99%